MODERN METHODS OF DIAGNOSING MENTAL DEVELOPMENT IN CHILDREN - Ergasheva Gulshoda Amirovna (Bright Mind Publishing, 2025)
The article presents information on modern approaches to diagnosing mental development. Also, issues such as modern methods and approaches to diagnosing mental development, problems and relevance of early study of the level of mental development of children, theoretical foundations of diagnosing mental development of children are discussed.
Keywords: Mental development, talent, ability, mental development, intellect, mental growth.